2006
DOI: 10.1002/app.23830
|View full text |Cite
|
Sign up to set email alerts
|

Anti‐ultraviolet and physical properties of woolen fabrics cured with citric acid and TiO2/chitosan

Abstract: This experiment is to research the chemical compositions of the crosslink of the woolen, oxidized with H 2 O 2 of various concentrations and temperatures, cured with the citric acid and TiO 2 /chitosan liquid of different proportions, and then observed by means of Fourier Transfer Infrared Spectrometer (FT-IR), Scanning Electronic Microscope (SEM), Energy Dispersive Spectrometer (EDS), and Thermo-Gravity Analyzer (TGA). Its antishrinkage, antimicrobes, antiultraviolet, strength, elasticity, softness, and yello… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 14 publications
1
22
0
Order By: Relevance
“…Zhao et al have reported that adding an optimum weight ratio of hydroxyl propyl cellulose (HPC) to TiO 2 nano-particles can improve the photoinduced hydrophilicity and the photo-catalytic activity of the TiO 2 film [95]. Anti-UV and other physical properties of TiO 2 /chitosan nano-composite have been reported by Hsieh et al [105].…”
Section: Tio 2 Nano-particlesmentioning
confidence: 94%
See 1 more Smart Citation
“…Zhao et al have reported that adding an optimum weight ratio of hydroxyl propyl cellulose (HPC) to TiO 2 nano-particles can improve the photoinduced hydrophilicity and the photo-catalytic activity of the TiO 2 film [95]. Anti-UV and other physical properties of TiO 2 /chitosan nano-composite have been reported by Hsieh et al [105].…”
Section: Tio 2 Nano-particlesmentioning
confidence: 94%
“…The production of Pt/TiO 2 [100], TiO 2 /chitosan nano-composites [105], TiO 2 /SiO 2 [106], CNTs-TiO 2 composites [107][108][109], TiO 2 -hydroxyapatite [110] and many others has also been reported.…”
Section: Tio 2 Nano-particlesmentioning
confidence: 99%
“…This is because of their ability to absorb ultraviolet irradiation and act as photo catalyst. Furthermore, nano TiO 2 particles on the fabric surfaces will not affect their breathability or handle 1–9. Various methods can be used to apply finishing materials on fabrics, including spraying, transfer printing, foaming, and padding among which padding is the most commonly used 10–17…”
Section: Introductionmentioning
confidence: 99%
“…Compared with the spectrum of the untreated wool fibers, the O-H band of the TiO2 coated wool fibers shifts from 3425 to 3443 cm -1 . This is ascribed to the surface absorbed water induced by the TiO2 coating [25], which might make the TiO2 coated fiber generate much stronger oxidative free radicals than those of untreated one [26]. …”
Section: Ft-ir Analysismentioning
confidence: 99%